LONG TERM HYDROLOGIC BALANCE OF THE CITARUM BASIN AND JAVA ISLANDKESEIMBANGAN HIDROLOGI JANGKA PANJANG DAS CITARUM DAN PULAU JAWA - Hidayat Pawitan (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2002)
Abstract is available in the full text (pdf format)